Efektivitas Penggunaan Anggaran Di Pusat Kesehatan Masyarakat Gelumbang Kabupaten Muara Enim - Merryati, Merryati; Novaria, Eva; Sandy, Amiruddin (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2025)
The Gelumbang District Muara Enim Community Health Center, in terms of budget utilization, strives to use the available budget in accordance with the applicable regulations, to ensure the smooth operation of the Gelumbang Community Health Center, in order to provide the best possible service to the service users. The issues arising in the budget utilization at the Gelumbang District Muara Enim Community Health Center are caused by several factors, resulting in the addition of unutilized funds (known as